Perinatal outcomes of pregestational hypertension according to blood pressure range at 11–14 week scan: Impact of the 2017 ACC/AHA guidelines - Sepúlveda-Martínez, Alvaro; Conrads, Tomas; Guiñez, Rodolfo; Guiñez, Javiera; Llancaqueo, Marcelo; Parra-Cordero, Mauro (Frontiers in Medicine, 2022)
Objective: to evaluate the impact on perinatal outcomes related with placental insufficiency, by the application of the new 2017 ACC / AHA guidelines to a group of chronic hypertensive pregnancies during their first trimester assessment. Study design: this retrospective cohort study included pregnancies with pre-conceptional hypertension and known perinatal outcome. At first trimester a combined screening for preterm preeclampsia (p-PE) was performed, including blood pressure (BP), mean uterine artery Doppler and maternal characteristics. Patients were divided, according to the 2017 ACC/AHA Consensus, in elevated or less, Stage 1 and Stage 2. For adverse perinatal outcome assessment, a univariate and multivariate regression analysis was performed, considering “Elevated or less” group as a reference. Odds ratios (OR) were compared with a linear trend analysis. Main Outcomes measured were preterm PE and FGR < 3rd percentile. Results: of 130 included patients, 59 (45.4%) were classified as Elevated or less, 47 (36.2%) as Stage 1 and 24 (18.4%) as Stage 2. p-PE showed a significant increase according to BP range (7% [OR= 1.0], 19.6% [OR= 3.2] and 21.7% [OR= 3.7]; trend p= 0.02, for Elevated or less, Stage 1 and Stage 2, respectively. There was a non-significant increased trend of FGR < 3rd percentile according to BP stage. The best multivariate predictive model for p-PE included a previous PE background (OR= 15) and mean arterial pressure in mmHg (OR= 1.1). Conclusion: the use of the 2017 ACC/AHA Consensus in pregnancies with chronic hypertension identifies an intermediate risk group for placental mediated diseases.